Causes of head injury in Dr. Hasan Sadikin General Hospital Bandung in 2015 - Rongkai, Tan; Arifin, M. Zafrullah; Prajitno, Ihrul Prianza (International Journal Of Community Medicine And Public Health, 2019)
Background: The study aimed to describe the causes of head injury (HI) in Rumah Sakit Hasan Sadikin Bandung with the considerations of gender, age and the severity of HI. Methods: This was a descriptive retrospective study. The study subjects were HI patients in Department of Neurosurgery of Dr. Hasan Sadikin General Hospital Bandung in 2015. Consecutive sampling was used with minimum sample size of 97 patients. The variables of the study were patients’ characteristics, causes of head injury, and types of road traffic accidents in HI patients. The data were collected from medical records. Results: Road traffic accidents (RTAs) contributed to 70.3% mild HI, 77.2% moderate HI, and 100% severe HI and it was the highest cause of HI (73%). Two-wheelers motor vehicle contributed to 62.5% mild HI, 75% moderate HI, and 66.7 severe HI and it was the highest cause of RTAs (68%). Majority of the HI patients were male (57%). The highest number of HI was 18-45 years old. Conclusions: RTAs is the main mechanism of HI, while two-wheelers motor vehicle is the main cause of RTAs.